2014
DOI: 10.1007/s12094-014-1241-3
|View full text |Cite
|
Sign up to set email alerts
|

The protein kinase C (PKC) inhibitors combined with chemotherapy in the treatment of advanced non-small cell lung cancer: meta-analysis of randomized controlled trials

Abstract: The use of PKC inhibitors in addition to chemotherapy was not a valid alternative for patients with advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Three decades later, it became apparent that not only were they not working as anti-cancer drugs, but in some cases, PKC inhibitors were worsening patient outcome. Most striking, a meta-analysis of five clinical trials for non-small cell lung carcinomas revealed worsened patient outcome when PKC inhibitors (enzastaurin, an ATP competitive inhibitor, or aprinocarsen, a PKCα antisense oligonucleotide) were combined with chemotherapy compared with chemotherapy alone (Zhang et al 2015). Thus, clinical trials unveiled a disconnect between the biology of phorbol esters and the presumed function of PKC.…”
Section: Pkc and Cancermentioning
confidence: 99%
“…Three decades later, it became apparent that not only were they not working as anti-cancer drugs, but in some cases, PKC inhibitors were worsening patient outcome. Most striking, a meta-analysis of five clinical trials for non-small cell lung carcinomas revealed worsened patient outcome when PKC inhibitors (enzastaurin, an ATP competitive inhibitor, or aprinocarsen, a PKCα antisense oligonucleotide) were combined with chemotherapy compared with chemotherapy alone (Zhang et al 2015). Thus, clinical trials unveiled a disconnect between the biology of phorbol esters and the presumed function of PKC.…”
Section: Pkc and Cancermentioning
confidence: 99%
“…However, these efforts were largely unsuccessful. Indeed, a meta analysis of five clinical trials for non-small cell lung carcinoma revealed that patient outcome worsened when PKC inhibitors were combined with chemotherapy compared to chemotherapy alone [12]. Why the disconnect?…”
Section: Phorbol Estersmentioning
confidence: 99%
“…Based on the dogma that PKC isozymes contribute positively to cancer progression, many PKC inhibitors have entered clinical trials; however, they have been ineffective (Mackay and Twelves, 2007). In fact, a recent meta-analysis of controlled trials of PKC inhibitors combined with chemotherapy versus chemotherapy alone revealed that PKC inhibitors significantly decreased response rates and disease control rates in non-small cell lung cancer (Zhang et al, 2014). Why has inhibiting PKC failed in the clinic?…”
Section: Introductionmentioning
confidence: 99%